2018
DOI: 10.1039/c8ra01265b
|View full text |Cite
|
Sign up to set email alerts
|

Laccase immobilization and surface modification of activated carbon fibers by bio-inspired poly-dopamine

Abstract: In this study, we developed a new synthesis method for modifying activated carbon fibers (ACFs) by dopamine with oxidation-based self-polymerization (DA-ACFs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Immobilization process may block laccase active sites and thereby decrease enzyme substrate affinity and maximize reaction rate (Antecka et al 2018). Low V max for laccase immobilized on both surface modified and unmodified activated carbon fibers were reported by (Zhang et al 2018).…”
Section: Kinetic Constants Of Free and Immobilized Enzymementioning
confidence: 99%
“…Immobilization process may block laccase active sites and thereby decrease enzyme substrate affinity and maximize reaction rate (Antecka et al 2018). Low V max for laccase immobilized on both surface modified and unmodified activated carbon fibers were reported by (Zhang et al 2018).…”
Section: Kinetic Constants Of Free and Immobilized Enzymementioning
confidence: 99%
“…This occurred because most of the AOX was adsorbed on the surface of the activated carbon. Thus, the active sites on the surface were occupied and further adsorption was inhibited [36]. We therefore concluded that the optimal activated carbon dosage to achieve maximum AOX removal efficiency was 1.75 g l −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This occurred because most of the AOX was adsorbed on the surface of the activated carbon. Thus, the active sites on the surface were occupied and further adsorption was inhibited [36]. We therefore concluded that the optimal adsorption capacity (mg g -1 ) 0 where q e is the adsorption capacity (mg g 21 ) and C e is the AOX concentration after adsorption (mg l 21 ).…”
Section: Effect Of the Activated Carbon Dosage On The Adsorption Capacitymentioning
confidence: 94%
“…Enzyme immobilization is defined as the attachment of soluble enzymes to a support material that results in the reduction or total loss in mobility of the attached enzyme [13]. Immobilizing laccase on various supports can protect them from denaturation, improve their stability, maintain good catalytic efficiency, facilitate efficient recovery and lead to more economical process [10] [14]. Thus, it is important to define an appropriate and suitable support for laccase immobilization [10].…”
Section: Methods Of Laccase Immobilizationmentioning
confidence: 99%